Physiological demands of mountain rescue work. Issue 9 (29th September 2011) - Callender, Nigel; Ellerton, John; Macdonald, Jamie Hugo
Abstract : Objective: To characterise the physical fitness of mountain rescue (MR) volunteers and the physical demands of a typical MR callout. Methods: Eight MR volunteers (age ± SD: 45.5 ± 8.9 years) completed a laboratory-based treadmill exercise test to exhaustion. One week later subjects completed a field-based simulated callout to retrieve a casualty by stretcher. In both studies exercise intensity was evaluated by determination of oxygen uptake and other cardiovascular measures. Results: The maximal oxygen uptake of the participants was 53 ml/kg/min (95% CI 45 to 60). In an unassisted callout, a typical rucksack load was 17% of body mass. Ascent time was 56 min (95% CI 40 to 72), of which 82% (95% CI 66% to 98%) was completed at hard or very hard intensity (above the respiratory compensation point). Descent time with a stretcher was 58 min (95% CI 52 to 64), of which only 6% (95% CI −4% to 16%) was completed at hard or very hard intensity. Correlations between heart rate and oxygen uptake were similar (p=0.254 by analysis of variance) during laboratory ( r =0.72) and field testing, especially for the ascent ( r =0.75). Conclusions: Mountain rescuers generally have high levels of physical fitness and are required to perform at very hard intensity for the majority of the ascent to a casualty. Heart rate is a simple yet valid measure of exercise intensity in MR personnel. These findings highlight important information on the unique physical demands faced by MR volunteers and provide direction for future research, volunteer selection and training.